SWOT ANALYSIS OF TRANSHIPMENT RELAXATION IMPACT ON MEASURED FISHING PROGRAM (PIT) POLICY IMPLEMENTATION - Purwanto, Hadi; Suharta; Bintoro, Sigit; Pratama, Fajar Surya; Maulana, Irwan (Departemen PSP IPB, 2025)
The Ministry of Maritime Affairs and Fisheries prioritizes measured fishing policy. The shift from pre-production to post-production fishing policy is unprecedented in Indonesia. The initial fisheries product levy (PHP) is now paid after the fishing operation based on fish species and amount. The Measured Fishing (PIT) mandated in Government Regulation 11 of 20203 has unnerved fishing businesses. The Minister of Maritime Affairs and Fisheries of Indonesia issued Circular (SE) B.1954/MEN-KP/XI/2023 to allow fishing vessels to tranship their catches at sea. This study employed SWOT. SWOT analysis plans outcomes. S is strength, W is weakness, O is opportunity, T is threat. This study used SWOT analysis to recommend using a good Fishing Vessel Monitoring System to help the Measured Fishing Program (MFP) to catch fish effectively and legally. The PIT program manages and regulates fishing to not exceed available resources and prevent illegal or detrimental fishing, improves port infrastructure to reduce IUU fishing with a stricter reporting system, improves catch data accuracy by using new technology to monitor and record fish types and numbers, and improves policy implementation and supervision to prevent climate change from harming mariculture. Key words: transhipment, Measured Fishing Program (MFP), post-production